Application of the envelope peaks over threshold (EPOT) method for probabilistic assessment of dynamic stability. (1st July 2016) - Campbell, Bradley; Belenky, Vadim; Pipiras, Vladas
Abstract: This paper reviews the research and development of the Envelope Peaks over Threshold (EPOT) method that has taken place in the last three years. The EPOT method is intended for the statistical extrapolation of ship motions and accelerations from time-domain numerical simulations, or possibly, from a model test. To model the relationship between probability and time, the large roll angle events must be independent, so Poisson flow can be used. The method uses the envelope of the signal to ensure the independence of large exceedances. The most significant development was application of the generalized Pareto Distribution (GPD) for approximation of the tail, replacing the previously used Weibull distribution. This paper reviews the main aspects of modeling the GPD, including its mathematical justification, fitting the parameters of the distribution, and evaluating the probability of exceedance and its confidence interval. Highlights: Development of the Envelope Peaks over Threshold (EPOT) for large roll is reviewed. Peaks of envelope is used to avoid dependence of consecutive peaks of roll motion. Generalized Pareto distribution is used to approximate the tail of peak distribution.